A GIS‐based model to estimate citrus pulp availability for biogas production: an application to a region of the Mediterranean Basin. (26th September 2016) - Valenti, Francesca; Porto, Simona MC; Chinnici, Gaetano; Cascone, Giovanni; Arcidiacono, Claudia
Abstract: In recent years, biogas from biomasses has increasingly been considered a feasible alternative to energy from fossil fuel. The utilization of biomasses obtained from citrus processing for juice extraction is being investigated for energy purposes, as a biofuel or organic matrix for bioethanol or biogas extraction, besides for the extraction of high added‐value by‐products and animal feed. In citrus producing areas, uncertainty often exists as to the amount of processed product and, therefore, correct planning of the use of 'citrus pulp' for energy purposes has not yet been carried out. The objective of this study was to analyze the spatial distribution of the citrus fruit production area and the amount of processed citrus in order to quantify the citrus pulp available for biogas production. It could contribute to build an information base suitable for multi‐criteria analysis aimed at finding optimal locations for biogas plants and increasing their number in a territory. The GIS‐based methodology, which was applied to the case study of citrus pulp production in Sicily, included official statistics data and information derived from specific surveys and the computation of indicators regarding citrus‐producing areas, citrus production, processed production, and the amount of citrus pulp obtained. The results showed that the index that describes the level of availability of citrus pulp for biogas production is suitable to provide information on the potential production of citrus pulp in the different areas of the whole territory analyzed. Furthermore, the total amount of available citrus pulp corresponded theoretically to 15, 204, 775.8 Nm 3 biogas. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd